Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3791/57665
|View full text |Cite
|
Sign up to set email alerts
|

Using Graphene Liquid Cell Transmission Electron Microscopy to Study <em>in Situ</em> Nanocrystal Etching

Abstract: Graphene liquid cell electron microscopy provides the ability to observe nanoscale chemical transformations and dynamics as the reactions are occurring in liquid environments. This manuscript describes the process for making graphene liquid cells through the example of graphene liquid cell transmission electron microscopy (TEM) experiments of gold nanocrystal etching. The protocol for making graphene liquid cells involves coating gold, holey-carbon TEM grids with chemical vapor deposition graphene and then usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 40 publications
0
71
0
Order By: Relevance
“…In these liquid cell transmission electron microscopy (TEM) experiments, premade gold nanocrystals are added to an aqueous solution of FeCl 3 and Tris-HCl, and the solution is encapsulated between graphene sheets for imaging in the TEM. 53 The concentrations of FeCl 3 are low enough that the gold nanocrystals do not begin to be etched until electron beam irradiation reaches a sufficiently high dose rate. Through a combination of the preloaded FeCl 3 and beam-induced radiolysis species, the nanocrystals undergo oxidative etching and the nanocrystals' etching trajectories can be observed ( Figure 1A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these liquid cell transmission electron microscopy (TEM) experiments, premade gold nanocrystals are added to an aqueous solution of FeCl 3 and Tris-HCl, and the solution is encapsulated between graphene sheets for imaging in the TEM. 53 The concentrations of FeCl 3 are low enough that the gold nanocrystals do not begin to be etched until electron beam irradiation reaches a sufficiently high dose rate. Through a combination of the preloaded FeCl 3 and beam-induced radiolysis species, the nanocrystals undergo oxidative etching and the nanocrystals' etching trajectories can be observed ( Figure 1A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Graphene liquid cells were fabricated following a reported procedure. 53 Graphene (3−5 layers, ACS materials) was transferred onto holey amorphous carbon, gold quantifoil TEM grids (SPI Supplies, 300 mesh, R1.2/1.3), and these grids were used to encapsulate a solution of 104 mM FeCl 3 (Sigma-Aldrich) in 22 mM HCl (Fisher Chemical), 100 mM tris-(hydroxymethyl)aminomethane hydrochloride, Tris-HCl, (Fisher Biotech), and the nanocrystals of interest. The volumes of FeCl 3 / HCl and Tris-HCl were modulated to yield the desired final FeCl 3 concentration.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the first approach, the liquid is encapsulated in a cavity between two Si 3 N 4 membranes produced via Si process technology 17 , whereas in the second, small liquid pockets are formed between two graphene or graphene oxide sheets 10,18 . The handling of both silicon-based liquid cells (SiLCs) and graphene-based liquid cells (GLCs) has been demonstrated 19,20,21 . Although both approaches have undergone significant improvements 22,23,24,25 , they still lack in the combination of the respective advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the prevalence of particle dissolution proves that a wet-chemical reaction is present which would not be possible without a successful liquid enclosing. Other typical indications for enclosed liquids are beam-induced bubble formation19 or particle motion. The presence of Au particles in graphene-featured cells alone does not conclusively indicate a liquid environment, since the particles could also stem from the graphene-induced reduction of HAuCl 4 A quantification of the oxygen peaks of the enclosed liquid via electron energy loss spectroscopy (EELS) can also be performed to verify a liquid environment41.…”
mentioning
confidence: 99%
“…We obtained the highest number of intact microtubules with the graphene coated sample supports. It was recently reported that the number of stable liquid pockets obtained in a graphene liquid cell strongly depends of the solvent conditions [7]. Figure 1a shows the schematic representation of graphene-encapsulated microtubules for electron microscopy.…”
mentioning
confidence: 98%